Subtype‐specific differences in transmission cluster dynamics of HIV‐1 B and CRF01_AE in New South Wales, Australia. Issue 1 (20th January 2021) - Di Giallonardo, Francesca; Pinto, Angie N; Keen, Phillip; Shaik, Ansari; Carrera, Alex; Salem, Hanan; Selvey, Christine; Nigro, Steven J; Fraser, Neil; Price, Karen; Holden, Joanne; Lee, Frederick J; et al.
Abstract: Introduction: The human immunodeficiency virus 1 (HIV‐1) pandemic is characterized by numerous distinct sub‐epidemics (clusters) that continually fuel local transmission. The aims of this study were to identify active growing clusters, to understand which factors most influence the transmission dynamics, how these vary between different subtypes and how this information might contribute to effective public health responses. Methods: We used HIV‐1 genomic sequence data linked to demographic factors that accounted for approximately 70% of all new HIV‐1 notifications in New South Wales (NSW). We assessed differences in transmission cluster dynamics between subtype B and circulating recombinant form 01_AE (CRF01_AE). Separate phylogenetic trees were estimated using 2919 subtype B and 473 CRF01_AE sequences sampled between 2004 and 2018 in combination with global sequence data and NSW‐specific clades were classified as clusters, pairs or singletons. Significant differences in demographics between subtypes were assessed with Chi‐Square statistics. Results: We identified 104 subtype B and 11 CRF01_AE growing clusters containing a maximum of 29 and 11 sequences for subtype B and CRF01_AE respectively. We observed a > 2‐fold increase in the number of NSW‐specific CRF01_AE clades over time. Subtype B clusters were associated with individuals reporting men who have sex with men (MSM) as their transmission risk factor, being born in Australia, and being diagnosed during the early stage of infection ( p  < 0.01). CRF01_AE infections clusters were associated with infections among individuals diagnosed during the early stage of infection ( p  < 0.05) and CRF01_AE singletons were more likely to be from infections among individuals reporting heterosexual transmission ( p  < 0.05). We found six subtype B clusters with an above‐average growth rate (>1.5 sequences / 6‐months) and which consisted of a majority of infections among MSM. We also found four active growing CRF01_AE clusters containing only infections among MSM. Finally, we found 47 subtype B and seven CRF01_AE clusters that contained a large gap in time (>1 year) between infections and may be indicative of intermediate transmissions via undiagnosed individuals. Conclusions: The large number of active and growing clusters among MSM are the driving force of the ongoing epidemic in NSW for subtype B and CRF01_AE.